Estudo da contextualização em provas de química: um olhar sobre o vestibular da universidade federal de Uberlândia e o exame nacional do ensino médio - Hipólito, Aline Fernandes (2012)
This paper presents a qualitative and quantitative nature documentary, uestions of chemistry of National Secondary Education Examination (Enem) and vestibular Federal University of Uberlândia (UFU) in the period of 2001-2010. After mapping the evidence and mount a database, which analyzed the material focusing on the contextual approaches that were focused on issues of chemistry, as well as possible interdisciplinary and cross situations. We used several authors for reasons of our discussions that seek to investigate: How contextual approaches are arranged on the issues of chemical vestibular Federal University of Uberlândia (UFU) and the National Secondary Education Examination Average (Enem)? Which focus, theme and show interest in these approaches and how they relate to the chemical content present in these processes? To this end, we divide the analysis in some parts, we observe, first, the relationship between phenomena, theories and chemical representations , seeking to understand how knowledge emerges from the chemical structure of scientific knowledge, correlating, and levels of chemical and relations involving the axes constituting fundamental chemical transformations, the materials and their properties and explanatory models. We also look for the presence or absence of interdisciplinarity and transversality, and the possible influences of these issues in chemistry, and the presence of some other contextual approaches that could be part of these issues. The results indicate a predominance of questions of General Chemistry (HQ), which shows that both tests select students who has a broader view of chemical knowledge, but to dominate and skills that make up each task. However, the analysis to detail about how knowledge emerges from the chemical structure of scientific knowledge, we note that the issues from both the vestibular UFU as Enem, reference levels and the axes of the chemical constituent, however, the slightly differently. The Enem presents both levels as the axes constituent in isolation, thus hampering the construction of knowledge by students. Since the vestibular UFU can merge more levels within the issues, working also in a less separated axes, which can help in the construction of chemical knowledge. We also investigate the more specific context of trying to find such evidence in the presence of at least some forms of context, which will certainly serve to enrich the questions. However, both studies the relationships bring technological, social and environmental, as a mere illustration of the theories and scientific concepts. When we think in relations with the daily and experimentation, this scenario is somewhat different, because both contextual approaches only appear in most issues of the two tests, when carrying out subsequent to the start of the New Enem.Also evaluated the presence of both interdisciplinarity as the transverse and the possible influences of them on these issues, which is explicit and ratified in Enem, which presents a series of cross-cutting issues, especially on the topic Environment. The Health theme also appeared in some issues, but in smaller proportions. Interdisciplinarity was also evident on several issues Enem, which makes clear the concern of the examination to correlate to the subjects, causing students to gain knowledge of how to build the most extensive and complete. However, when we look at the issues of chemical vestibular UFU, we could not find cross-cutting issues, interdisciplinary or what we prevented a more detailed study of the subject, this selection process. Thus, we see that both tests have strengths and weaknesses, the questions of chemistry. However, the contextual approaches appear subtly in both selection processes, mainly in the analysis made in recent years. This fact may show that some changes are occurring in these tests and the contextual approaches are becoming priority in the preparation of these issues, which may assist in a closer knowledge of chemicals linked to student s lives.